2010
DOI: 10.1267/ahc.09032
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of the Stem Cell Factor Receptor c-kit in Alopecia Areata and Androgenetic Alopecia: Histopathological, Immunohistochemical, and Semiquantitative Investigations

Abstract: Alopecia areata (AAR) and androgenetic alopecia (AGA) are two major forms of alopecia based on altered hair growth condition. In general, the cell cycle is regulated by several mechanisms including the stem cell factor/c-kit signaling. To assess a role for stem cell activity in alopecia, we performed histopathological, immunohistochemical, and semiquantitative analyses of c-kit as well as Ki-67 in scalp biopsy specimens obtained from 14 patients with AAR, 18 patients with AGA, and 6 age-matched control subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In addition, the mean number of c‐kit‐immunoreactive cells per follicle was significantly increased. This upregulation may reflect a negative feedback mechanism in response to possible downregulation of the ligand stem cell factor similar to that seen in AGA in the same study 29 . Stem cell involvement was demonstrated in two elderly women with AA with unusual lymphocytic cell infiltrates surrounding both the bulge and the bulbar regions.…”
Section: Nonscarring Alopeciasupporting
confidence: 54%
See 1 more Smart Citation
“…In addition, the mean number of c‐kit‐immunoreactive cells per follicle was significantly increased. This upregulation may reflect a negative feedback mechanism in response to possible downregulation of the ligand stem cell factor similar to that seen in AGA in the same study 29 . Stem cell involvement was demonstrated in two elderly women with AA with unusual lymphocytic cell infiltrates surrounding both the bulge and the bulbar regions.…”
Section: Nonscarring Alopeciasupporting
confidence: 54%
“…In addition, another study by Ashrafuzzaman et al. 29 showed that the mean length of hair follicles was significantly shorter in the AGA groups than in the control group and similarly the mean number of Ki‐67‐immunoreactive cells per follicle was significantly reduced. Another report has indicated that mice lacking in functional vitamin D receptors develop a functional first coat of hair but lack the cyclic regeneration of hair follicles, leading to the development of alopecia 30 .…”
Section: Nonscarring Alopeciamentioning
confidence: 92%
“…Androgenic alopecia (AGA) is a common type of hair loss, which is known as the result of interaction between 5a-DHT level and genetic predisposition [ 143 ]. Several researches have indicated the roles of HFTs in the onset of AGA [ 144 , 145 ]. However, not all types of HFTs but the specific CD200-rich and CD34-positive HFSCs are mainly in deficiency in the bald scalp of AGA patients [ 146 ].…”
Section: Emerging Roles In Non-malignant Skin Disordersmentioning
confidence: 99%
“…There have been number of immunohistochemical markers used to study or to detect the bulge regions of the hair follicles but many of them such as Ki‐67 and c‐kit fail to show specific staining of the bulge area. While several markers have been reported positive for the vicinity of the bulge stem cells including one for CD 200 and CD34, the clone C8/144b of cytokeratin 15 has consistently demonstrated the bulge stem cell region and it is known to show normal hair differentiation in in vitro study .…”
Section: Discussionmentioning
confidence: 99%